La razón de Estado en Giovanni Botero: Una teología política entre omnipotencia y contingencia - Miceli, Mario Leonardo (2018)
The paper tries to study the way in which the Piedmontese clergyman Giovanni Botero develops the concept of «Reason of State» through a series of works published in the late sixteenth and early seventeenth centuries. The hypothesis attempts to demonstrate how this intellectual reproduces an art of government based on the practical application of medieval principles, in his path to deal with the urging political and social problems of his time, emerging as a consequence ideas that could be approached from a modern perspective but always having in mind the strong bonds with medieval thought structures. Particularly, the article explains how his theory lays on a political theology which, on the one hand recreates an almost omnipotent power, close to the modern idea of sovereignty, but on the other enrolls this same power within a medieval frame where politics is centered in the idea of contingency and subordinates itself to juridical and religious precepts.